Green environment-friendly heat-resistant photovoltaic cable and preparation method thereof
By using specific components of insulating layer and sheathing layer materials in photovoltaic cables to form a multi-dimensional network structure, the drip problem during combustion of photovoltaic cables is solved, the flame retardant performance and thermal stability are improved, and the fire spread is reduced.
Patent Information
- Application Number
- CN202510716216.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-12
AI Technical Summary
Existing photovoltaic cables are prone to drips when burning, expand the range of fire, and have limited flame retardant performance.
The insulating layer and sheath layer are composed of components such as polylactic acid, polyhydroxy fatty acid esters, halogen-free flame-retardant crosslinked polyethylene, and other materials, combined with modified graphene, quaternary ammonium chitosan nanofibers, lignin-based carbon nanotubes and other materials, to form a multi-dimensional network structure to improve flame retardant performance and thermal stability.
Effectively suppress melt dripping during combustion, reduce heat release rate, improve heat resistance and flame retardant effect, and reduce economic losses during combustion.
Smart Images

Figure BDA0005428282770000111 
Figure BDA0005428282770000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic cables, and in particular to a green, environmentally friendly, heat-resistant photovoltaic cable and a preparation method thereof. Background Art
[0002] Photovoltaic cable is a cable specially used in solar photovoltaic power generation systems. It has the characteristics of high temperature resistance, UV resistance, and environmental stress resistance. It is a key component in solar system connecting components, inverters and other equipment, and is mainly used for DC side power transmission.
[0003] Green, environmentally friendly and heat-resistant photovoltaic cables are cables with specific performance improvements for photovoltaic cables. They have the characteristics of high temperature resistance, environmental protection and non-toxicity, and strong weather resistance. They are suitable for power transmission in complex environments.
[0004] The functions of photovoltaic cables in existing general technologies are usually relatively simple, with only simple heat resistance, anti-aging and other properties. They also have limited flame retardancy and are prone to produce dripping after combustion. The dripping produced by combustion ignites other combustibles below, expanding the scope of the fire and causing large economic losses. Summary of the Invention
[0005] In response to the problems existing in the prior art, the present invention provides a green, environmentally friendly, heat-resistant photovoltaic cable and a preparation method thereof.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] The present application discloses a green, environmentally friendly, heat-resistant photovoltaic cable, comprising a conductor, an insulating layer, and a sheath layer, which are sequentially arranged from the inside out. The insulating layer comprises the following raw materials, measured by weight percentage: 20-30% polylactic acid, 10-20% polyhydroxyalkanoate, 25-35% halogen-free flame-retardant cross-linked polyethylene, 5-15% phosphated lignin microspheres, 3-8% quaternized chitosan nanofibers, 1-3% modified graphene, 2-6% epoxidized soybean oil, 1-5% modified montmorillonite, 0.5-1.5% nano-silica aerogel, 2-4% sodium alginate microcapsules, 0.5-1.5% polydimethylsiloxane, 0.1-0.8% silane coupling agent, and 0.1-0.8% plant polyphenol antioxidant.
[0008] The sheath layer includes raw materials of the following components: 45-55% of halogen-free flame-retardant cross-linked polyethylene, 10-20% of lignin-based carbon nanotubes, 5-15% of sulfonated chitosan / sodium alginate microspheres, 1-6% of graphene, 5-15% of epoxy soybean oil, 2-8% of nano-silica, 1-3% of polydimethylsiloxane, 1-3% of peppermint oil microcapsules, 1-3% of silane coupling agent, 0.1-0.8% of antioxidant, and 0.1-0.8% of ultraviolet absorber.
[0009] Preferably, the insulating layer comprises the following raw materials, measured by weight percentage: 25% polylactic acid, 15% polyhydroxyalkanoate, 30% halogen-free flame-retardant cross-linked polyethylene, 10% phosphated lignin microspheres, 5% quaternized chitosan nanofibers, 2% modified graphene, 4% epoxidized soybean oil, 3% modified montmorillonite, 1% nano-silica aerogel, 3% sodium alginate microcapsules, 1% polydimethylsiloxane, 0.5% silane coupling agent, and 0.5% plant polyphenol antioxidant;
[0010] The sheath layer includes the following raw materials: 50% halogen-free flame retardant cross-linked polyethylene, 15% lignin-based carbon nanotubes, 10% sulfonated chitosan / sodium alginate microspheres, 3% graphene, 10% epoxy soybean oil, 5% nano-silica, 2% polydimethylsiloxane, 2% peppermint oil microcapsules, 2% silane coupling agent, 0.5% antioxidant, and 0.5% ultraviolet absorber.
[0011] Preferably, the preparation method of phosphated lignin microspheres is as follows:
[0012] a1) 5 g of lignin and 10 ml of dimethyl sulfoxide were stirred at 70°C for 10 min, then the temperature was lowered to a constant level of 30°C. 6 ml of phosphorus oxychloride was slowly added dropwise. After the addition was complete, the temperature was raised to 50°C and stirred for 2 h. The reaction solution was poured into 200 mL of ethanol, centrifuged at high speed, and the precipitate was collected. The precipitate was then washed once with ethanol and dissolved in 50 mL of acetone. 1 mL of epichlorohydrin was added, stirred, and set aside.
[0013] a2) dissolving 3 g of polyvinyl alcohol in 100 mL of water, heating to 80° C. to dissolve, cooling to room temperature, then slowly adding the material obtained in step a1) thereto, stirring at 1500 rpm for 3 h to form an emulsion, centrifuging at 5000 rpm for 5 min, and washing twice with water and ethanol;
[0014] a3) drying the precipitate obtained in step a2) at 40° C. for 12 h, and pulverizing the precipitate through an 80-100 mesh sieve to obtain the product.
[0015] Preferably, the preparation method of quaternized chitosan nanofibers is as follows:
[0016] b1) dissolving 5 g of chitosan in 100 mL of 5% acetic acid solution and stirring until clear, then slowly adding 2 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride and stirring in a 60° C. water bath for 4-6 h. Then, sodium bicarbonate solution was added to adjust the pH to 8-9, and the precipitate was washed three times with ethanol and lyophilized to obtain quaternized chitosan powder;
[0017] b2) quaternary ammonium salt chitosan powder is dissolved in 1-3% acetic acid solution, 1%-2% polyvinyl alcohol is added, and magnetic stirring is performed for 2-3 hours. The mixture is allowed to stand for degassing for 30 minutes, and then melt-spun at 12-18 kV, a needle diameter of 0.8-1.2 mm, a receiving distance of 10-15 cm, and a flow rate of 0.5-1.5 mL / h to obtain quaternary ammonium salt chitosan nanofibers.
[0018] Preferably, the preparation method of modified graphene is as follows: electrochemical exfoliation of graphite, oxidation treatment with H2O2 / concentrated H2SO4 in a volume ratio of 1:3 for 4 hours, followed by loading phosphotungstic acid in a mass ratio of 1:1, and purification by dialysis to obtain modified graphene with a particle size of 8-12 nm.
[0019] Preferably, the preparation method of modified montmorillonite is as follows:
[0020] c1) adding 10 g of montmorillonite to 200 mL of deionized water and dispersing the mixture under ultrasonic conditions of 200 W and 40 kHz for 30 min to form a montmorillonite suspension;
[0021] c2) dissolving 7.5 g of lecithin in 50 mL of a 1:1 ethanol-water mixture by volume, stirring in a 60° C. water bath until clarified, then slowly adding the mixture to the montmorillonite suspension, stirring at 300 rpm for 4 h at a constant temperature of 70° C. to form a flocculent precipitate, centrifuging at high speed, and then washing with deionized water 2-3 times until the supernatant is free of free lecithin;
[0022] c3) Dry the precipitate in an oven at 60°C for 12 hours, grind it through a 100-mesh sieve, and obtain modified montmorillonite.
[0023] Preferably, the preparation method of sodium alginate microcapsules is as follows: ammonium polyphosphate and 2% sodium alginate solution are evenly mixed in a mass ratio of 1:3, and sodium alginate microcapsules are obtained by spray drying; the preparation method of lignin-based carbon nanotubes is as follows: lignin and Fe(NO3)3 are mixed in a mass ratio of 10:1, carbonized in an N2 atmosphere at 800°C for 2h, and then C2H4 and H2 are introduced at a volume ratio of 1:4 at 650°C to grow 5-15μm CNTs for 30min.
[0024] Preferably, the peppermint oil microcapsules are made of peppermint oil and lemongrass oil in a mass ratio of 1:1.
[0025] This application also discloses a method for preparing a green, environmentally friendly, heat-resistant photovoltaic cable, comprising the following steps:
[0026] S1. Add polylactic acid, polyhydroxyalkanoate, and halogen-free flame-retardant cross-linked polyethylene into a twin-screw extruder and blend at 450 r / min for 6 min at 210-220°C;
[0027] S2. Add the extrudate obtained in step S1 and the remaining materials into a three-stage single-screw extruder, melt-extrude at 210-215° C. and 20 MPa at a speed of 60 r / min, and vacuum-size the insulation layer to control the thickness of the insulation layer to 1.2 mm. Wrap the conductor with the insulation layer;
[0028] S3. Add the raw materials for preparing the jacket layer into an internal mixer, mix them at 150° C. and 100 r / min for 18 min, and then use a twin-screw extruder at a pressure of 22 MPa and a speed of 70 r / min to prepare the jacket layer using a double-layer co-extrusion die.
[0029] Preferably, the plant polyphenol antioxidant is rosemary extract.
[0030] The beneficial effects of the present invention are:
[0031] Electrochemically exfoliated graphite and surface-loaded with phosphotungstic acid form a PW synergistic flame retardant system, significantly improving thermal conductivity. Chemical vapor deposition (CVD) grows carbon nanotubes on the lignin surface, forming a three-dimensional network that increases tensile strength and volume resistivity. Electrochemically exfoliated graphite, lignin-based carbon nanotubes, sodium alginate microcapsules, and nano-modified montmorillonite form a four-dimensional network that inhibits melt dripping and reduces heat release rate.
[0032] Quaternized chitosan nanofibers exhibit antibacterial and synergistic flame retardancy. Grafted with dodecyldimethylbenzyl ammonium chloride, they promote charring during combustion. Epoxidized soybean oil acts as a plasticizer and crosslinker. Maleic anhydride-modified epoxidized soybean oil in situ crosslinks with polylactic acid, increasing crosslink density.
[0033] Dodecyldimethylbenzyl ammonium chloride modified nano-montmorillonite enhances barrier properties, reduces oxygen transmission rate, and suppresses dripping during combustion. Polydimethylsiloxane, a surface modifier, migrates to the surface to form a low-energy surface layer, improving stain resistance and self-extinguishing properties. Sulfonated chitosan / sodium alginate microspheres are flame retardant synergists that expand into a char layer during combustion, suppressing dripping. Peppermint oil microcapsules have a strong rodent repellent effect. DETAILED DESCRIPTION
[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.
[0035] Example 1:
[0036] This embodiment discloses a green, environmentally friendly, heat-resistant photovoltaic cable, comprising a conductor, an insulation layer, and a sheath layer, which are sequentially arranged from the inside out. The insulation layer comprises the following components, in weight percentage: 24.8% polylactic acid, 10% polyhydroxyalkanoate, 35% halogen-free flame-retardant cross-linked polyethylene, 15% phosphated lignin microspheres, 8% quaternized chitosan nanofibers, 1% modified graphene, 2% epoxidized soybean oil, 1% modified montmorillonite, 0.5% nano-silica aerogel, 2% sodium alginate microcapsules, 0.5% polydimethylsiloxane, 0.1% silane coupling agent, and 0.1% rosemary extract.
[0037] The sheath layer includes the following raw materials: 53.8% halogen-free flame-retardant cross-linked polyethylene, 20% lignin-based carbon nanotubes, 15% sulfonated chitosan / sodium alginate microspheres, 1% graphene, 5% epoxy soybean oil, 2% nano-silica, 1% polydimethylsiloxane, 1% peppermint oil microcapsules, 1% silane coupling agent, 0.1% antioxidant, and 0.1% ultraviolet absorber. Among them, the peppermint oil microcapsules are made of peppermint oil and lemongrass oil in a mass ratio of 1:1.
[0038] The preparation method of phosphated lignin microspheres is as follows:
[0039] a1) 5 g of lignin and 10 ml of dimethyl sulfoxide were stirred at 70°C for 10 min, then the temperature was lowered to a constant level of 30°C. 6 ml of phosphorus oxychloride was slowly added dropwise. After the addition was complete, the temperature was raised to 50°C and stirred for 2 h. The reaction solution was poured into 200 mL of ethanol, centrifuged at high speed, and the precipitate was collected. The precipitate was then washed once with ethanol and dissolved in 50 mL of acetone. 1 mL of epichlorohydrin was added, stirred, and set aside.
[0040] a2) dissolving 3 g of polyvinyl alcohol in 100 mL of water, heating to 80° C. to dissolve, cooling to room temperature, then slowly adding the material obtained in step a1) thereto, stirring at 1500 rpm for 3 h to form an emulsion, centrifuging at 5000 rpm for 5 min, and washing twice with water and ethanol;
[0041] a3) drying the precipitate obtained in step a2) at 40° C. for 12 h, and pulverizing the precipitate through an 80-100 mesh sieve to obtain the product.
[0042] The preparation method of quaternized chitosan nanofibers is as follows:
[0043] b1) dissolving 5 g of chitosan in 100 mL of 5% acetic acid solution and stirring until clear, then slowly adding 2 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride and stirring in a 60° C. water bath for 4-6 h. Then, sodium bicarbonate solution was added to adjust the pH to 8-9, and the precipitate was washed three times with ethanol and lyophilized to obtain quaternized chitosan powder;
[0044] b2) quaternary ammonium salt chitosan powder is dissolved in 1-3% acetic acid solution, 1%-2% polyvinyl alcohol is added, and magnetic stirring is performed for 2-3 hours. The mixture is allowed to stand for degassing for 30 minutes, and then melt-spun at 12-18 kV, a needle diameter of 0.8-1.2 mm, a receiving distance of 10-15 cm, and a flow rate of 0.5-1.5 mL / h to obtain quaternary ammonium salt chitosan nanofibers.
[0045] The preparation method of modified graphene is as follows: electrochemical exfoliation of graphite, oxidation treatment with H2O2 / concentrated H2SO4 in a volume ratio of 1:3 for 4 hours, followed by loading with phosphotungstic acid in a mass ratio of 1:1, and purification by dialysis to obtain modified graphene with a particle size of 8-12 nm.
[0046] The preparation method of modified montmorillonite is as follows:
[0047] c1) adding 10 g of montmorillonite to 200 mL of deionized water and dispersing the mixture under ultrasonic conditions of 200 W and 40 kHz for 30 min to form a montmorillonite suspension;
[0048] c2) dissolving 7.5 g of lecithin in 50 mL of a 1:1 ethanol-water mixture by volume, stirring in a 60° C. water bath until clarified, then slowly adding the mixture to the montmorillonite suspension, stirring at 300 rpm for 4 h at a constant temperature of 70° C. to form a flocculent precipitate, centrifuging at high speed, and then washing with deionized water 2-3 times until the supernatant is free of free lecithin;
[0049] c3) Dry the precipitate in an oven at 60°C for 12 hours, grind it through a 100-mesh sieve, and obtain modified montmorillonite.
[0050] The preparation method of sodium alginate microcapsules is as follows: ammonium polyphosphate and 2% sodium alginate solution are uniformly mixed in a mass ratio of 1:3, and the sodium alginate microcapsules are obtained by spray drying.
[0051] The preparation method of lignin-based carbon nanotubes is as follows: lignin and Fe(NO3)3 are mixed in a mass ratio of 10:1, carbonized for 2 hours in a N2 atmosphere at 800℃, and then C2H4 and H2 are introduced in a volume ratio of 1:4 at 650℃ to grow 5-15μm CNTs for 30 minutes.
[0052] This embodiment also discloses a method for preparing a green, environmentally friendly, heat-resistant photovoltaic cable, comprising the following steps:
[0053] S1. Add polylactic acid, polyhydroxyalkanoate, and halogen-free flame-retardant cross-linked polyethylene into a twin-screw extruder and blend at 450 r / min for 6 min at 210-220°C;
[0054] S2. Add the extrudate obtained in step S1 and the remaining materials into a three-stage single-screw extruder, melt-extrude at 210-215° C. and 20 MPa at a speed of 60 r / min, and vacuum-size the insulation layer to control the thickness of the insulation layer to 1.2 mm. Wrap the conductor with the insulation layer;
[0055] S3. Add the raw materials for preparing the jacket layer into an internal mixer, mix them at 150° C. and 100 r / min for 18 min, and then use a twin-screw extruder at a pressure of 22 MPa and a speed of 70 r / min to prepare the jacket layer using a double-layer co-extrusion die.
[0056] Example 2:
[0057] This embodiment discloses a green, environmentally friendly, heat-resistant photovoltaic cable, which differs from the embodiment only in the difference in the proportions of the various components. Specifically, the insulating layer comprises the following raw materials, measured by weight percentage: 20% polylactic acid, 10% polyhydroxyalkanoate, 25% halogen-free flame-retardant cross-linked polyethylene, 15% phosphated lignin microspheres, 8% quaternized chitosan nanofibers, 3% modified graphene, 5.4% epoxidized soybean oil, 5% modified montmorillonite, 1.5% nano-silica aerogel, 4% sodium alginate microcapsules, 1.5% polydimethylsiloxane, 0.8% silane coupling agent, and 0.8% rosemary extract.
[0058] The sheath layer includes raw materials of the following components: 45.4% halogen-free flame-retardant cross-linked polyethylene, 10% lignin-based carbon nanotubes, 5% sulfonated chitosan / sodium alginate microspheres, 6% graphene, 15% epoxy soybean oil, 8% nano-silica, 3% polydimethylsiloxane, 3% peppermint oil microcapsules, 3% silane coupling agent, 0.8% antioxidant, and 0.8% ultraviolet absorber. Among them, the peppermint oil microcapsules are made of peppermint oil and lemongrass oil in a mass ratio of 1:1.
[0059] Example 3:
[0060] This embodiment discloses a green, environmentally friendly, heat-resistant photovoltaic cable, which differs from the embodiment only in the proportions of the components. Specifically, the insulating layer comprises the following raw materials, measured by weight: 25% polylactic acid, 15% polyhydroxyalkanoate, 30% halogen-free flame-retardant cross-linked polyethylene, 10% phosphated lignin microspheres, 5% quaternized chitosan nanofibers, 2% modified graphene, 4% epoxidized soybean oil, 3% modified montmorillonite, 1% nano-silica aerogel, 3% sodium alginate microcapsules, 1% polydimethylsiloxane, 0.5% silane coupling agent, and 0.5% plant polyphenol antioxidant.
[0061] The sheath layer includes the following raw materials: 50% halogen-free flame-retardant cross-linked polyethylene, 15% lignin-based carbon nanotubes, 10% sulfonated chitosan / sodium alginate microspheres, 3% graphene, 10% epoxy soybean oil, 5% nano-silica, 2% polydimethylsiloxane, 2% peppermint oil microcapsules, 2% silane coupling agent, 0.5% antioxidant, and 0.5% ultraviolet absorber. Among them, the peppermint oil microcapsules are made of peppermint oil and lemongrass oil in a mass ratio of 1:1.
[0062] Comparative Example 1:
[0063] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that polylactic acid is not added to the insulation layer, and the remaining components are increased in proportion to a total component content of 100%.
[0064] Comparative Example 2:
[0065] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that no polyhydroxyalkanoate is added to the insulation layer, and the remaining components are increased in proportion to a total component content of 100%.
[0066] Comparative Example 3:
[0067] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that the insulating layer does not contain phosphated lignin microspheres, and the remaining components are increased in proportion to a total content of 100%.
[0068] Comparative Example 4:
[0069] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that the insulating layer does not contain quaternary ammonium salt chitosan nanofibers, and the remaining components are increased in proportion to a total component content of 100%.
[0070] Comparative Example 5:
[0071] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that the insulating layer does not contain modified graphene, and the remaining components are increased in proportion to a total component content of 100%.
[0072] Comparative Example 6:
[0073] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that ordinary graphene is used instead of modified graphene, and the remaining components are increased in proportion to a total component content of 100%.
[0074] Comparative Example 7:
[0075] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that no epoxy soybean oil is added to the insulation layer, and the remaining components are increased in proportion to a total component content of 100%.
[0076] Comparative Example 8:
[0077] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that no modified montmorillonite is added to the insulation layer, and the remaining components are increased in proportion to a total component content of 100%.
[0078] Comparative Example 9:
[0079] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that ordinary montmorillonite is used instead of modified montmorillonite, and the remaining components are increased in proportion to a total component content of 100%.
[0080] Comparative Example 10:
[0081] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that sodium alginate microcapsules are not added to the insulation layer, and the remaining components are increased in proportion to a total component content of 100%.
[0082] Comparative Example 11:
[0083] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that polydimethylsiloxane is not added to the insulation layer, and the remaining components are increased in proportion to a total component content of 100%.
[0084] Comparative Example 12:
[0085] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that no rosemary extract is added to the insulation layer, and the remaining components are increased in equal proportions until the total component content is 100%.
[0086] Comparative Example 13:
[0087] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that no lignin-based carbon nanotubes are added to the sheath layer, and the remaining components are increased in proportion to a total component content of 100%.
[0088] Comparative Example 14:
[0089] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that the sheath layer does not contain sulfonated chitosan / sodium alginate microspheres, and the remaining components are increased in equal proportions until the total content is 100%.
[0090] Comparative Example 15:
[0091] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that no epoxy soybean oil is added to the sheath layer, and the remaining components are increased in proportion to a total component content of 100%.
[0092] Comparative Example 16:
[0093] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that nano-silicon dioxide is not added to the sheath layer, and the remaining components are increased in proportion to a total component content of 100%.
[0094] Comparative Example 17:
[0095] A green, environmentally friendly, heat-resistant photovoltaic cable. The difference between the photovoltaic cable and Example 3 is that peppermint oil microcapsules are not added to the sheath layer, and the remaining components are increased in proportion to a total component content of 100%.
[0096] The photovoltaic cables obtained in the above Examples 1-3 and Comparative Examples 1-17 were subjected to performance tests to measure the comprehensive performance of the photovoltaic cables. The results are shown in Table 1.
[0097] Table 1 Performance parameters of photovoltaic cables obtained in Examples 1-3 and Comparative Examples 1-17
[0098]
[0099]
[0100] In summary, electrochemically exfoliated graphite and surface-loaded phosphotungstic acid (PTTA) form a synergistic flame retardant system, significantly improving thermal conductivity. Chemical vapor deposition (CVD) grows carbon nanotubes (CNTs) on the lignin surface, forming a three-dimensional network that increases tensile strength and volume resistivity. Electrochemically exfoliated graphite, lignin-based CNTs, sodium alginate microcapsules, and nano-modified montmorillonite form a four-dimensional network that inhibits melt dripping and reduces heat release rate.
[0101] Quaternized chitosan nanofibers exhibit antibacterial and synergistic flame retardancy. Grafted with dodecyldimethylbenzyl ammonium chloride, they promote charring during combustion. Epoxidized soybean oil acts as a plasticizer and crosslinker. Maleic anhydride-modified epoxidized soybean oil in situ crosslinks with polylactic acid, increasing crosslink density.
[0102] Dodecyldimethylbenzyl ammonium chloride modified nano-montmorillonite enhances barrier properties, reduces oxygen transmission rate, and suppresses dripping during combustion. Polydimethylsiloxane, a surface modifier, migrates to the surface to form a low-energy surface layer, improving stain resistance and self-extinguishing properties. Sulfonated chitosan / sodium alginate microspheres are flame retardant synergists that expand into a char layer during combustion, suppressing dripping. Peppermint oil microcapsules have a strong rodent repellent effect.
[0103] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. A green, environmentally friendly, heat-resistant photovoltaic cable, characterized in that: The invention comprises a conductor, an insulating layer and a sheath layer which are sequentially arranged from the inside out. The insulating layer comprises the following raw materials by weight: 20-30% of polylactic acid, 10-20% of polyhydroxyalkanoate, 25-35% of halogen-free flame-retardant cross-linked polyethylene, 5-15% of phosphated lignin microspheres, 3-8% of quaternized chitosan nanofibers, 1-3% of modified graphene, 2-6% of epoxy soybean oil, 1-5% of modified montmorillonite, 0.5-1.5% of nano-silica aerogel, 2-4% of sodium alginate microcapsules, 0.5-1.5% of polydimethylsiloxane, 0.1-0.8% of silane coupling agent, and 0.1-0.8% of plant polyphenol antioxidant. The sheath layer includes raw materials of the following components: 45-55% of halogen-free flame-retardant cross-linked polyethylene, 10-20% of lignin-based carbon nanotubes, 5-15% of sulfonated chitosan / sodium alginate microspheres, 1-6% of graphene, 5-15% of epoxy soybean oil, 2-8% of nano-silica, 1-3% of polydimethylsiloxane, 1-3% of peppermint oil microcapsules, 1-3% of silane coupling agent, 0.1-0.8% of antioxidant, and 0.1-0.8% of ultraviolet absorber.
2. The green, environmentally friendly, heat-resistant photovoltaic cable according to claim 1, characterized in that: The insulating layer comprises the following raw materials, measured by weight percentage: 25% polylactic acid, 15% polyhydroxyalkanoate, 30% halogen-free flame-retardant cross-linked polyethylene, 10% phosphated lignin microspheres, 5% quaternized chitosan nanofibers, 2% modified graphene, 4% epoxidized soybean oil, 3% modified montmorillonite, 1% nano-silica aerogel, 3% sodium alginate microcapsules, 1% polydimethylsiloxane, 0.5% silane coupling agent, and 0.5% plant polyphenol antioxidant; The sheath layer includes the following raw materials: 50% halogen-free flame retardant cross-linked polyethylene, 15% lignin-based carbon nanotubes, 10% sulfonated chitosan / sodium alginate microspheres, 3% graphene, 10% epoxy soybean oil, 5% nano-silica, 2% polydimethylsiloxane, 2% peppermint oil microcapsules, 2% silane coupling agent, 0.5% antioxidant, and 0.5% ultraviolet absorber.
3. The green, environmentally friendly, heat-resistant photovoltaic cable according to claim 1 or 2, characterized in that: The preparation method of phosphated lignin microspheres is as follows: a1) 5 g of lignin and 10 ml of dimethyl sulfoxide were stirred at 70°C for 10 min, then the temperature was lowered to a constant level of 30°C. 6 ml of phosphorus oxychloride was slowly added dropwise. After the addition was complete, the temperature was raised to 50°C and stirred for 2 h. The reaction solution was poured into 200 mL of ethanol, centrifuged at high speed, and the precipitate was collected. The precipitate was then washed once with ethanol and dissolved in 50 mL of acetone. 1 mL of epichlorohydrin was added, stirred, and set aside. a2) dissolving 3 g of polyvinyl alcohol in 100 mL of water, heating to 80° C. to dissolve, cooling to room temperature, then slowly adding the material obtained in step a1) thereto, stirring at 1500 rpm for 3 h to form an emulsion, centrifuging at 5000 rpm for 5 min, and washing twice with water and ethanol; a3) drying the precipitate obtained in step a2) at 40° C. for 12 h, and pulverizing the precipitate through an 80-100 mesh sieve to obtain the product.
4. The green, environmentally friendly, heat-resistant photovoltaic cable according to claim 3, characterized in that: The preparation method of quaternized chitosan nanofibers is as follows: b1) dissolving 5 g of chitosan in 100 mL of 5% acetic acid solution and stirring until clear, then slowly adding 2 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride and stirring in a 60° C. water bath for 4-6 h. Then, sodium bicarbonate solution was added to adjust the pH to 8-9, and the precipitate was washed three times with ethanol and lyophilized to obtain quaternized chitosan powder; b2) quaternary ammonium salt chitosan powder is dissolved in 1-3% acetic acid solution, 1%-2% polyvinyl alcohol is added, and magnetic stirring is performed for 2-3 hours. The mixture is allowed to stand for degassing for 30 minutes, and then melt-spun at 12-18 kV, a needle diameter of 0.8-1.2 mm, a receiving distance of 10-15 cm, and a flow rate of 0.5-1.5 mL / h to obtain quaternary ammonium salt chitosan nanofibers.
5. The green, environmentally friendly, heat-resistant photovoltaic cable according to claim 4, characterized in that: The preparation method of modified graphene is as follows: electrochemical exfoliation of graphite, oxidation treatment with H2O2 / concentrated H2SO4 in a volume ratio of 1:3 for 4 hours, followed by loading with phosphotungstic acid in a mass ratio of 1:1, and purification by dialysis to obtain modified graphene with a particle size of 8-12 nm.
6. The green, environmentally friendly, heat-resistant photovoltaic cable according to claim 5, characterized in that: The preparation method of modified montmorillonite is as follows: c1) adding 10 g of montmorillonite to 200 mL of deionized water and dispersing the mixture under ultrasonic conditions of 200 W and 40 kHz for 30 min to form a montmorillonite suspension; c2) dissolving 7.5 g of lecithin in 50 mL of a 1:1 ethanol-water mixture by volume, stirring in a 60° C. water bath until clarified, then slowly adding the mixture to the montmorillonite suspension, stirring at 300 rpm for 4 h at a constant temperature of 70° C. to form a flocculent precipitate, centrifuging at high speed, and then washing with deionized water 2-3 times until the supernatant is free of free lecithin; c3) Dry the precipitate in an oven at 60°C for 12 hours, grind it through a 100-mesh sieve, and obtain modified montmorillonite.
7. The green, environmentally friendly, heat-resistant photovoltaic cable according to claim 5, characterized in that: The preparation method of sodium alginate microcapsules is as follows: ammonium polyphosphate and 2% sodium alginate solution are uniformly mixed in a mass ratio of 1:3, and the sodium alginate microcapsules are obtained by spray drying; The preparation method of lignin-based carbon nanotubes is as follows: lignin and Fe(NO3)3 are mixed in a mass ratio of 10:1, carbonized for 2 hours in a N2 atmosphere at 800℃, and then C2H4 and H2 are introduced in a volume ratio of 1:4 at 650℃ to grow 5-15μm CNTs for 30 minutes.
8. The green, environmentally friendly, heat-resistant photovoltaic cable according to claim 5, characterized in that: Peppermint oil microcapsules are made of peppermint oil and lemongrass oil in a mass ratio of 1:
1.
9. A method for preparing a green, environmentally friendly, heat-resistant photovoltaic cable according to any one of claims 1 to 8, characterized in that: The steps are as follows: S1. Add polylactic acid, polyhydroxyalkanoate, and halogen-free flame-retardant cross-linked polyethylene into a twin-screw extruder and blend at 450 r / min for 6 min at 210-220°C; S2. Add the extrudate obtained in step S1 and the remaining materials into a three-stage single-screw extruder, melt-extrude at 210-215° C. and 20 MPa at a speed of 60 r / min, and vacuum-size the insulation layer to control the thickness of the insulation layer to 1.2 mm. Wrap the conductor with the insulation layer; S3. Add the raw materials for preparing the jacket layer into an internal mixer, mix them at 150° C. and 100 r / min for 18 min, and then use a twin-screw extruder at a pressure of 22 MPa and a speed of 70 r / min to prepare the jacket layer using a double-layer co-extrusion die.
10. The green, environmentally friendly, heat-resistant photovoltaic cable according to claim 5, characterized in that: The plant polyphenol antioxidant is rosemary extract.
Citation Information
Cited By
Hydrophobic anti-icing material based on silver ions and application of hydrophobic anti-icing material in power transmission line
CN121203537A
Silane naturally-crosslinked flame-retardant TPE cable material and preparation method thereof
CN121930573A